Saline irrigation for chronic rhinosinusitis - Chong, Lee Yee; Head, Karen; Hopkins, Claire; Philpott, Carl; Glew, Simon; Scadding, Glenis; Burton, Martin J; Schilder, Anne G M (Cochrane database of systematic reviews, 2016)
This review is one of six looking at the primary medical management options for patients with chronic rhinosinusitis.Chronic rhinosinusitis is common and is characterised by inflammation of the lining of the nose and paranasal sinuses leading to nasal blockage, nasal discharge, facial pressure/pain and loss of sense of smell. The condition can occur with or without nasal polyps. Nasal saline irrigation is commonly used to improve patient symptoms. To evaluate the effects of saline irrigation in patients with chronic rhinosinusitis. The Cochrane ENT Information Specialist searched the ENT Trials Register; Central Register of Controlled Trials (CENTRAL 2015, Issue 9); MEDLINE; EMBASE; ClinicalTrials.gov; ICTRP and additional sources for published and unpublished trials. The date of the search was 30 October 2015. Randomised controlled trials (RCTs) with a follow-up period of at least three months comparing saline delivered to the nose by any means (douche, irrigation, drops, spray or nebuliser) with (a) placebo, (b) no treatment or (c) other pharmacological interventions. We used the standard methodological procedures expected by Cochrane. Our primary outcomes were disease-specific health-related quality of life (HRQL), patient-reported disease severity and the commonest adverse event - epistaxis. Secondary outcomes included general HRQL, endoscopic nasal polyp score, computerised tomography (CT) scan score and the adverse events of local irritation and discomfort. We used GRADE to assess the quality of the evidence for each outcome; this is indicated in italics. We included two RCTs (116 adult participants). One compared large-volume (150 ml) hypertonic (2%) saline irrigation with usual treatment over a six-month period; the other compared 5 ml nebulised saline twice a day with intranasal corticosteroids, treating participants for three months and evaluating them on completion of treatment and three months later. Large-volume, hypertonic nasal saline versus usual care One trial included 76 adult participants (52 intervention, 24 control) with or without polyps.Disease-specific HRQL was reported using the Rhinosinusitis Disability Index (RSDI; 0 to 100, 100 = best quality of life). At the end of three months of treatment, patients in the saline group were better than those in the placebo group (mean difference (MD) 6.3 points, 95% confidence interval (CI) 0.89 to 11.71) and at six months there was a greater effect (MD 13.5 points, 95% CI 9.63 to 17.37). We assessed the evidence to be of low quality for the three months follow-up and very low quality for the six months follow-up. Patient-reported disease severity was evaluated using a "single-item sinus symptom severity assessment" but the range of scores is not stated, making it impossible for us to determine the meaning of the data presented.No adverse effects data were collected in the control group but 23% of participants in the saline group experienced side effects including epistaxis. General HRQL was measured using SF-12 (0 to 100, 100 = best quality of life). No difference was found after three months of treatment (low quality evidence) but at six months there was a small difference favouring the saline group, which may not be of clinical significance and has high uncertainty (MD 10.5 points, 95% CI 0.66 to 20.34) (very low quality evidence). Low-volume, nebulised saline versus intranasal corticosteroids One trial included 40 adult participants with polyps. Our primary outcome of disease-specific HRQL was not reported. At the end of treatment (three months) the patients who had intranasal corticosteroids had less severe symptoms (MD -13.50, 95% CI -14.44 to -12.56); this corresponds to a large effect size. We assessed the evidence to be of very low quality. The two studies were very different in terms of included populations, interventions and comparisons and so it is therefore difficult to draw conclusions for practice. The evidence suggests that there is no benefit of a low-volume (5 ml) nebulised saline spray over intranasal steroids. There is some benefit of daily, large-volume (150 ml) saline irrigation with a hypertonic solution when compared with placebo, but the quality of the evidence is low for three months and very low for six months of treatment.